Tendency of Gap Opening in Semimetal 1T′‐MoTe2 with Proximity to a 3D Topological Insulator. (20th June 2021) - Zhang, Cheng; Liu, Wei; Zhan, Fangyang; Zhang, Teng; Liu, Liwei; Zhang, Min; Xie, Sen; Li, Ziwei; Sang, Hao; Ge, Haoran; Yan, Yonggao; Wang, Rui; et al.
Abstract: Monolayer (ML) 1T′‐MoTe2 has attracted intensive interest as a fascinating quantum spin Hall (QSH) insulator. However, there are two critical aspects impeding its exploration and potential applications of QSH effects. One is its semimetallic feature with a negative band gap, leading to nontrivial edge channels annihilated by the bulk states. The other is its fabrication always accompanied by a mixed phase of 1T′ and 2H. Based on first‐principles calculations, it is shown that the large work‐function difference results in strong interlayer interactions and proximity effects in ML 1T′‐MoTe2 via interfacing a 3D topological insulator Bi2 Te3, facilitating the realization of pure 1T′ phase and even the band gap opening. It is further verified that the epi‐grown ML 1T′‐MoTe2 on Bi2 Te3 is nearly in single phase. Furthermore, the measurements of angle resolved photoemission spectroscopy and scanning tunneling spectroscopy confirm the obvious separated‐tendency of conduction and valence bands as well as the strong metallic edge states in ML 1T′‐MoTe2 . The results also reveal the nontrivial band topology in ML 1T′‐MoTe2 is preserved in 1T′‐MoTe2 /Bi2 Te3 heterostructure. This work offers a promising candidate to realize QSH effects and provides guidance for controlling the nontrivial band gap opening by proximity effects in van der Waals engineering. Abstract : The effective reduction of band overlap with nontrivial helical edge states is realized in semimetallic monolayer 1T′‐MoTe2 with proximity to a 3D topological insulator Bi2 Te3 . The charge transfer and interlayer interactions are theoretically and experimentally verified to be vital for the enhancements of spin orbital coupling, and thus the effective opening of the quantum spin Hall band gap of monolayer 1T′‐MoTe2 .